Pengaruh Penggunaan Google Classroom Terhadap Motivasi Belajar Dan Hasil Belajar Siswa Kelas 5 - Dewi Istiqomah; Muhammad Anasrulloh; Fajar Hendro Utomo; Dian Septi Nur Afiifah (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2026)
This study aims to determine the effect of Google Classroom  usage on IPAS learning outcomes, the effect of learning motivation on learning outcomes, and the role of learning motivation as a moderating variable in the relationship between Google Classroom  usage and learning outcomes of 5th-grade students in Cluster 1, Sutojayan District. The background of this research is based on the gap between the demands of educational digitalization and field conditions, where the utilization of learning applications is still low and student learning outcomes in IPAS subjects are not yet optimal. This research uses a quantitative approach with a cross-sectional survey design. The research subjects included 120 students of 5th-grade in eight elementary schools in Cluster 1, Sutojayan District. Data analysis techniques used descriptive and inferential statistics including prerequisite tests, t-test, F-test, and Moderated Regression Analysis (MRA). The results showed that: (1) there is a positive and significant influence of Google Classroom  usage on IPAS learning outcomes (t-count 7.031 > t-table 1.981); (2) there is a significant influence of learning motivation on IPAS learning outcomes (t-count 6.153); and (3) learning motivation significantly moderates and strengthens the influence of Google Classroom  usage on IPAS learning outcomes (interaction t-count 2.871). Simultaneously, these variables contributed an influence of 68.2% on learning outcomes